2022
DOI: 10.1007/s40615-021-01176-4
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Racial Attitudes and Associations Among Obstetricians in Hawaiʻi: a Pilot Study

Abstract: Introduction Pacific Islanders living in Hawai‘i with ancestral ties to islands in the western Pacific region of Micronesia are common targets of uninhibited forms of prejudice in multiple sectors, including healthcare. Whether the explicit societal-level attitudes toward this group are reflected in implicit attitudes among healthcare providers is unknown; therefore, we designed a pilot study to investigate this question. Our study measures implicit racial bias toward Pacific Islanders from Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…This study also found that IAT d-scores increased with increasing age, which may suggest greater levels of implicit bias in older populations. This finding is comparative to previous research suggesting aging may cause practitioners to rely more on stereotypes and neglect mindfulness 19,40,41 as aging decreases suppression of prejudicial thoughts or actions from consciousness, allowing implicit bias to be more easily expressed. 40 However, this finding should be interpreted with caution as the R 2 was 0.02, indicating that only 2% of the variability in d-score could be attributed to age.…”
Section: Findings Suggest That Dental Hygienists Practicing In the Un...contrasting
confidence: 89%
“…This study also found that IAT d-scores increased with increasing age, which may suggest greater levels of implicit bias in older populations. This finding is comparative to previous research suggesting aging may cause practitioners to rely more on stereotypes and neglect mindfulness 19,40,41 as aging decreases suppression of prejudicial thoughts or actions from consciousness, allowing implicit bias to be more easily expressed. 40 However, this finding should be interpreted with caution as the R 2 was 0.02, indicating that only 2% of the variability in d-score could be attributed to age.…”
Section: Findings Suggest That Dental Hygienists Practicing In the Un...contrasting
confidence: 89%
“…26,27 Implicit biases on the part of providers may contribute to unequal care and treatment of minority groups. [28][29][30] While there are evident disparities in diagnosed hypertension in Hawaiʻi, it remains unclear whether similar disparities exist for undiagnosed hypertension. In other words, are certain groups more likely to be missed than others?…”
Section: Introductionmentioning
confidence: 99%
“… 32 , 33 Implicit biases on the part of providers may contribute to unequal care and treatment of minority groups. 34 , 35 , 36 Although there are evident disparities of diagnosed hypertension in Hawaiʻi, it remains unclear whether similar disparities exist for undiagnosed hypertension. In other words, are certain groups more likely to be missed than others?…”
mentioning
confidence: 99%